مخاطر السمعة والالتزام بالشريعة في المصارف الإسلامية : دراسة حالة على الاحتياطيات في البنوك المركزية وكيفية تشكيل هيئات الرقابة الشرعية - أبو مؤنس، رائد نصري جميل (الجامعة الأردنية - عمادة البحث العلمي, 2016)
The risks reputation extent of compliance with the provisions of Islamic Sharia one of the risks facing the Islamic financial institutions without the other, which adds to the equation of profitability and liquidity risk and an additional factor in how to maintain customer confidence. The research aims to clarify the sensitivity of the management of the banks towards Reputational risks and Sharia compliance in Islamic banks Through a preference for options that have achieved even if it leads to lower levels of operations through deposits retained high levels of liquidity to maintain high reserves in central banks without charging any returns that have on them Model for risk management reputation and Sharia compliance. The study pointed out the criteria for selecting Sharia Supervisory Board. And the relationship of that reputational risks in Islamic banks. And the researcher presented a proposal for the management of Islamic banks in Jordan to work it constitutes a reinforcing rules of Islamic banking.
تعتبر مخاطر سمعة مدي الالتزام بأحكام الشريعة الإسلامية التي تواجه المؤسسات المالية الإسلامية دون غيرها، مما يضيف إلى معادلة الربحية والمخاطرة والسيولة عاملا إضافيا في كيفية الحفاظ على ثقة العملاء. ويهدف هذا البحث إلى بيان إشكالية حساسية إدارة المصارف تحو مخاطر سمعة الالتزام بأحكام الشريعة من خلال تفصيلها لخيارات تكفل لها ذلك، لو أدي ذلك لانخفاض مستويات عملات تشغيل الودائع من خلال الاحتفاظ بمستويات عالية من السيولة، ويعد الاحتفاظ باحتياطيات عالية في النوك المركزية دون تقاضي أي عوائد عليها أحد تطبيقات غدارة مخاطر الالتزام بالشريعة. وبينت الدراسة معايير اختيار هيئات الرقابة الشريعة، وعلاقة ذلك بمخاطر السمعة في المصارف الإسلامية. ويعمل البحاث في هذه الدراسة على بيان مقترح يمكن لإدارة المصارف الإسلامية في الأردن العمل وفقه بما يعزز قواعد المصرفية الإسلامية.
Keywords: البنوك الإسلامية -- الشريعة الإسلامية -- البنوك المركزية -- الرقابة الشرعية